Iron Deficiency Induces a Partial Inhibition of the Photosynthetic Electron Transport and a High Sensitivity to Light in the Diatom Phaeodactylum tricornutum - Roncel, Mercedes; González-Rodríguez, Antonio A.; Naranjo, Belén; Bernal-Bayard, Pilar; Lindahl, Anna M.; Hervás, Manuel; Navarro, José A.; Ortega, José M. (Frontiers in Plant Science, 2016)
Iron limitation is the major factor controlling phytoplankton growth in vast regions of the contemporary oceans. In this study, a combination of thermoluminescence, chlorophyll fluorescence and P700 absorbance measurements have been used to elucidate the effects of iron deficiency in the photosynthetic electron transport of the marine diatom Phaeodactylum tricornutum. Thermoluminescence was used to determine the effects of iron deficiency on Photosystem II activity. Excitation of iron-replete Phaeodactylum tricornutum cells with single turn-over flashes induced the appearance of thermoluminescence glow curves with two components with different peaks of temperature and contributions to the total signal intensity: the B band (23 ºC, 63%), and the AG band (40 ºC, 37%). Iron limitation did not significantly alter these bands, but induced a decrease of the total thermoluminescence signal. Far red excitation did not increase the amount of the AG band in iron-limited cells, as observed for iron-replete cells. The effect of iron deficiency on the photosystem I activity was also examined by measuring the changes in P700 redox state during illumination. The electron donation to photosystem I was substantially reduced in iron-deficient cells. This could be related with the important decline on cytochrome c6 content observed in these cells. Iron deficiency also induced a marked increase in light sensitivity in Phaeodactylum tricornutum cells. A drastic increase in the level of peroxidation of chloroplast lipids was detected in iron-deficient cells even when grown under standard conditions at low light intensity. Illumination with a light intensity of 300 E m-2 s-1 during different time periods caused a dramatic disappearance in thermoluminescence signal in cells grown under low iron concentration, this treatment not affecting to the signal in iron-replete cells. The results of this work suggest that iron deficiency induces partial blocking of the electron transfer between photosystem II and photosystem I, due to a lower concentration of the electron donor cytochrome c6. This decreased electron transfer may induce the over-reduction of the plastoquinone pool and consequently the appearance of acceptor side photoinhibition in photosystem II even at low light intensities. The functionality of chlororespiratory electron transfer pathway under iron restricted conditions is also discussed